Analisis Komparatif Perhitungan Waktu Salat Menggunakan Sistem Ephimeris dan Nautika - Nurul Atiqah; A.Intan Cahyani; Sohra (HISABUNA: Jurnal Ilmu Falak, 2023)
The purpose of this study is to: 1) find out the method of calculating prayer times based on the epimeris and nautical systems? 2) calculate the level of accuracy in calculating prayer times using the epimeris and nautical systems. This research is classified as Library Research. The results of the study, the authors found that 1). There are differences in the calculation of prayer times using the epimeris and nautical systems because the formulas and data sources used are different because the value of the equation of time and the meridian pass only uses the same value to calculate five times. 2). From the average results, the results obtained are the calculation of prayer times using the ephimeris and nautical systems with the prayer times throughout the Saado’eddin Djambek period as a comparison value, the results obtained are 1 minute 33 seconds of ephimeris data, and 4 minutes 3 seconds of nautical almanacs. After determining the calculation of prayer times using the comparison of the epimeris data system and the nautical almanac which has a difference of at least 1 minute 33 seconds is to use the ephimeris system, it can be said that using the ephimeris system the calculation results are more accurate than using the concept of calculating the nautical almanac.